Toward the Role of EFL/ESL Students’ Silence as a Facilitative Element in Their Success - Hu, Jing (Frontiers in Psychology, 2021)
Following the recent evolution of research perspectives towards student silence, an increasing number of studies have sought to empirically probe into the beneficial role of this variable in students’ success. Yet, a limited number of review articles have been carried out to illustrate the complex nature of student silence and its positive consequences (e.g., success, increased learning outcomes, etc.). Hence, the present study aims to review different definitions of ‘student silence’ to elucidate its facilitative function in EFL/ESL students’ success. Providing empirical evidence, the role of student silence as a facilitative element in English language learning was proved. Finally, some pedagogical implications for EFL/ESL teachers and teacher trainers are also discussed.